Employees' Perception towards Pygmalion-Oriented Leaders and Leader-Member Exchange in Commercial Banks - Acharya, Ganesh; Basnet, Dinesh (Journal of Business and Social Sciences Research, 2024)
Pygmalion-oriented leaders and Leaders Member Exchange (LMX) are the essential antecedents of employees' perception in an organisation, but they are less examined in prior research. Thus, this study examines the employees' view of Pygmalion-oriented leaders and LMX as it might pose a dyadic presentation. This study followed the positivist epistemology. A descriptive and causal research design has been used in this study. One hundred forty employees from commercial banks participated in this study. Responses were collected using a convenience sampling method. The study used correlation and regression to study the Pygmalion effect and LMX impact in shaping employees' perceptions. The findings of the study postulate that the Pygmalion-oriented leader and positive LMX have a significant impact on shaping the employees' perception. The findings of the study show that the Pygmalion effect and Leader Member Exchange has a considerable impact upon shaping the employees’ perception. This study's findings apply to the Nepalese context, specifically in the banking sector and the banking and financial institutions (BFIs) of Nepal. This study is imperative for accentuating the role of the Pygmalion effect and the essence of LMX in managing the BFIs and other big institutions of Nepal.